When children express their preferences regarding sales channels. Issue 11 (25th November 2014) - de Faultrier, Brigitte; Boulay, Jacques; de Faultrier, Brigitte; Feenstra, Florence; Muzellec, Laurent
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the preferences of children under the age of 12 regarding sales channels: how young consumers perceive online vs offline shopping in terms of advantages and disadvantages. Within a cross channel perspective, it also analyses the connections they make between brick-and-mortar and online stores. Design/methodology/approach – Results are drawn from an exploratory and qualitative study based on a multi-category approach. In all, 62 children (34 girls and 28 boys) aged six to 12 years were interviewed about the advantages and disadvantages of each channel for shopping; how/where they would prefer to shop and why; and the links they make between a brand's physical store and an online store. Findings – Traditional sales outlets are more popular with six to 12 year olds than online shopping. Physical stores offer variety and instant gratification. Products can be tried out and tested on-site, making the offline retail experience a fun activity. Conversely, children express a very negative perception of e-retailing, which they often consider to be dishonest, offering limited choice at higher prices. When shopping online, delivery time can be a deterrent. Last but not least, no cross-channel shopping perceptions were found. Practical implications – Several results from this study can inform marketing practices at retailers' headquarters. Store assortment, product availability and store atmospherics are central to the success of offline shopping among six- to 12-year-old children. Retailers should find ways to transfer this relational approach to their online strategy. In the meantime, they must deliver the same basic promises as in stores: a wide choice and competitive prices, no shortage of products and no late delivery. Originality/value – This study adds to the existing body of knowledge on children's consumer behaviour in three ways. First, it provides new insight into how children perceive not the internet per se but online shopping. Second, it confirms that stores still play a dominant role in shaping the image of a retail brand, from an early age. Third, it suggests that the cross-channel perspective may not apply to very young consumers.